2020
DOI: 10.1186/s12886-020-01563-1
|View full text |Cite
|
Sign up to set email alerts
|

Branch retinal artery occlusion secondary to high-altitude exposure and diabetic retinopathy: a case report

Abstract: Background To report a case of branch retinal artery occlusion (BRAO) secondary to high-altitude exposure and diabetic retinopathy (DR), and to characterize the retinal changes before and after hyperbaric oxygen (HBO) treatment. Case presentation We present a case of a 42-year-old man with DR who travelled to Tibet (in China, 3800 m/12467 ft. above mean sea level). The day after the end of his journey, the patient presented with acute, painless visual loss and visual fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Current reports showed that an extremely high Hct level may be associated with RAO [ 12 , 13 , 30 , 31 , 32 , 33 , 34 ]. Feng et al, has reported a case of BRAO in a high-altitude male climber with a Hct level of 52.4%; in addition, the man also had DM, which might be a predisposing factor for RAO [ 30 ]. Polycythemia vera, a hyperviscosity disease reflected in increased Hct, have been reported to cause RAO [ 12 , 13 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current reports showed that an extremely high Hct level may be associated with RAO [ 12 , 13 , 30 , 31 , 32 , 33 , 34 ]. Feng et al, has reported a case of BRAO in a high-altitude male climber with a Hct level of 52.4%; in addition, the man also had DM, which might be a predisposing factor for RAO [ 30 ]. Polycythemia vera, a hyperviscosity disease reflected in increased Hct, have been reported to cause RAO [ 12 , 13 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have suggested the beneficial effects of living at HA on glucose homeostasis, the relationship between HA and DR remains unclear owing to multiple factors and potential confounders, such as varying altitudes of the investigated population, duration of exposure to HA, genetic backgrounds, living conditions, dietary habits, and physiological adaptation. Table 1 summarizes the main findings of previous studies [9][10][11][12][13][14][15] that explored the impact of HA on DR. This review aimed to comprehensively explore the impact of HA exposure on DR, encompassing genetic adaptations, changes in glucose homeostasis, and related factors.…”
Section: Introductionmentioning
confidence: 99%